1996
DOI: 10.1159/000267910
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cytokine Gene Expression in Rat Retina following Transient Ischemia

Abstract: Tumor necrosis factor (TNF) gene expression in rat retina following transient ischemia was studied by semiquantitative reverse transcription-polymerase chain reaction (RT-PCR). Gene expression for other cytokines was also studied by RT-PCR. Although very little expression for TNF gene was detected in normal retina, it was markedly increased 0.5-48 h after reperfusion, with peak expression at 12 h (20-fold of control). Gene expression for interleukin-6, interferon-γ, and transforming growth factor-β1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…1c,f ). These results extend previous data on induction of TNF after retinal ischemia (Hangai et al, 1996) and identify the cell layers capable of TNF expression.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1c,f ). These results extend previous data on induction of TNF after retinal ischemia (Hangai et al, 1996) and identify the cell layers capable of TNF expression.…”
Section: Resultssupporting
confidence: 90%
“…Development of a brain ischemic lesion depends on the activation of many pathophysiological processes, dominating basal or concomitantly induced neuroprotective mechanisms (Maiese, 1998). Production and release of cytokines, particularly of TNF, is one of the early cellular events subsequent to an ischemic episode (Hangai et al, 1996;Shoshami et al, 1999). Because of its diverse bioactivities, it is presently not clear under which conditions TNF promotes beneficial or deleterious effects on neuronal tissues.…”
Section: Neurodegenerative and Neuroprotective Effects Of Tumor Necrosismentioning
confidence: 99%
“…Unlike VEGF, the aqueous level of IL-6 was not significantly correlated with the vitreous level of IL-6, although the aqueous level and vitreous level of IL-6 was significantly higher than the plasma level. It has been shown that a wide range of ocular tissues can produce IL-6 in vitro and in vivo, such as corneal epithelial cells and keratocytes, 31 iris and cilliary body explants, 32 cytokine-stimulated human pigment epithelial cells, 33,34 ischaemic retina, 35 and hypoxia-induced or cytokinestimulated vascular endothelial cells, and vascular smooth muscle cells. 36 Inflammatory cells, such as mast cells and macrophages, are known to be able to stimulate IL-6 secretion from leukocytes and human vascular endothelial cells in ischaemic and inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia leads disruption of the cellular energy metabolism and initiates several harmful cascades [1]. The generation of reactive oxygen species (ROS), degradation of the antioxidant system, induction of cytokine production via transcriptional factors, and extracellular accumulation of glutamate that is excitotoxic to neuronal elements are the main alterations secondary to ischemia [1,16,18,19,34,38,40,41]. Reperfusion after initial ischemia paradoxically maintains the destruction process, perhaps due to increased levels of extracellular neurotransmitters, ROS, and waste products damaging previously unharmed cells when being reoxidized [1,5,28].…”
Section: Introductionmentioning
confidence: 99%